2012
DOI: 10.1016/j.jsps.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of Arabic online drug information among adults in Saudi Arabia

Abstract: In Saudi Arabia, the utilization of the world wide web has become increasingly popular. However, the exact figure of such use is unknown. This study aimed to determine the percentage of, and experience with, online Arabic drug information by Arabic-speaking adults in Saudi Arabia. A web based questionnaire was used. The questionnaire language was Arabic. Public were invited to participate in the survey through e-mails, Twitter, WhatsApp and Facebook in March 2012. The survey included 17 items examining the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 5 publications
0
14
1
Order By: Relevance
“…The results are in accordance with previous studies focusing on health information, showing that the internet is used in particular by highly educated, relatively young women who use it daily [1][2]3,5 and those who continuously use vitamins and herbal remedies, even though some previous studies have not found differences between genders in internet use for health information purposes. 13 Chronic illnesses were not associated with increased internet use as a medicines information source in our study, which contrasts with previous studies 7,9,[17][18] and thus, needs to be explored further. This discrepancy may be due to methodological issues, as this survey was posted mainly by patient organizations yielding to a group of respondents who almost all had some chronic illness.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results are in accordance with previous studies focusing on health information, showing that the internet is used in particular by highly educated, relatively young women who use it daily [1][2]3,5 and those who continuously use vitamins and herbal remedies, even though some previous studies have not found differences between genders in internet use for health information purposes. 13 Chronic illnesses were not associated with increased internet use as a medicines information source in our study, which contrasts with previous studies 7,9,[17][18] and thus, needs to be explored further. This discrepancy may be due to methodological issues, as this survey was posted mainly by patient organizations yielding to a group of respondents who almost all had some chronic illness.…”
Section: Discussioncontrasting
confidence: 99%
“…6,[15][16] Furthermore, some studies have focused on the use of internet as MI source among people with some specific patient groups, such as mental illness, diabetes, high blood pressure and high cholesterol. 7,9,[17][18] More research is needed in order to comprehensively identify those groups who are the most active users of the online MI and who may especially benefit from internet-based MI sources and services in terms of sociodemographic factors (broader than gender and age), health status and medicine use This will help to focus development of internet-based MI sources and services for these groups.…”
Section: Internet As a Source Of Medicines Information (Mi) Among Frementioning
confidence: 99%
“…Five studies investigated the applicability of the WhatsApp Messenger as either a communication tool between health care professionals or as a learning tool [ 12 , 16 , 19 , 21 , 22 ]. In the other 5 studies, the app was used either as a communication tool between health care professionals and the public or as a teaching tool to provide information on health care to the general population [ 5 , 15 , 17 , 18 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…They were chosen because they are high-quality representative Web pages written in plain English and provide good linkages between medical terminology and plain English words [ 26 ]. A total of 30 articles were initially identified, but after a detailed assessment of all of the references, a subsequent screening, and a quality assessment, 10 studies were determined to be eligible for inclusion [ 5 , 12 , 15 - 22 ]. Although our study demonstrates a positive role of WhatsApp usage for health care purposes, the studies found in the literature were found to be substandard in quality.…”
Section: Discussionmentioning
confidence: 99%
“…All the reasons stated above make dosage recommendation, ADR, and drug interaction the most important DI that the clinicians can search for. 31,32 Based on the respondents' perceptions toward the type of DI in mobile medical applications, general dosage recommendations, pediatric dosage recommendations, and dosage recommendations in renal failure are among the most important information. A previous study indicates that dosage recommendations are the highest number of inquiries received in DI.…”
Section: Discussionmentioning
confidence: 99%